Electrolyte changes in the neonates receiving phototherapy - Purohit, Abhishek; Verma, Suresh Kumar (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal jaundice is the most commonly observed clinical condition of early neonatal period. It remains a common cause of readmission and important cause of concern for the parents and clinicians. Therefore, appropriate management of neonatal hyperbilirubinemia is of paramount importance. Phototherapy plays a significant role in its management but this modality is not devoid of complications. Authors studied electrolyte changes in the neonates, who received phototherapy. Methods: This perspective hospital based observational study conducted over the period of one year on 90 eligible admitted neonates who received phototherapy as per AAP guideline. Serum bilirubin, sodium, potassium and calcium were determined before and after termination of phototherapy. The first samples were considered as controls and compared with the samples collected after termination of phototherapy. Results: The incidence of LBW babies in this study was 21.9%, while mean birth weight and gestational age was2.76±0.38 kg and 38.34±0.88 weeks respectively. Mean duration of phototherapy was 38.48±09.34 hours. The mean sodium, potassium and calcium level before therapy were 146.6±6.2 mg/dl, 4.7±0.47 mg/dl and 9.4±0.73 mg/dl respectively. Authors found statistically significant changes in the electrolyte’s levels (Na+ 141.3±6.1, K+ 4.2±0.51 and Ca+2 8.4±0.68 respectively), after phototherapy however none of any neonate shown any clinical signs of dyselectolytemia. Conclusions: Neonates undergoing phototherapy are at greater risk of dyselectrolytemia especially in preterm babies therefore close clinical and biochemical monitoring is required for the prompt management of any significant electrolyte imbalance.